Artificial roosts for tree‐roosting bats in northern Arizona - Elisabeth D. Mering; Carol L. Chambers (Wildlife Society Bulletin)
Abstract Bats use large (69 cm mean diameter) ponderosa pine (Pinus ponderosa) snags for maternity roosts in northern Arizona. Anthropogenic causes have altered forest structure, decreasing density of large snags. To examine use of artificial roosts for bats in these forests, we selected 26 sites and 2 treatments (clustered, single) using 1 type of roost (resin or wood) per site. At each site, we installed 4 roosts on ponderosa pine trees with a cluster of 3 roosts (south‐, east‐, or west‐facing; <20 m apart) and a single roost (south‐facing) 250–350 m away. We checked roosts every 2 weeks for use (guano or bats) and monitored internal temperatures every 2 hours from May through September in 2009 and 2010. Bats used 52% of roosts (19 roosts in 2009, 49 in 2010) at least once and colonized resin roosts sooner than wood roosts. Sites with clustered resin roosts were used more than single roosts. Bats used south‐ and east‐facing resin roosts more and these had warmer average temperatures than west‐facing roosts. We captured 47 bats of 5 species using artificial roosts. We only captured male bats from roosts in 2009, juveniles and females were also captured in 2010 but no maternity roosts were documented. We recommend that resin roosts placed in clusters on live trees be used to supplement natural roosts in ponderosa pine forests. Because use increased with time we suspect artificial roosts may be used for several years before establishment of maternity colonies. Artificial roosts require annual maintenance (e.g., waterproofing) to maintain function and can be expensive to install and maintain. © 2012 The Wildlife Society.